Effect of mulch type on physico-chemical quality of tomato (Solanum lycopersicum) in semi-arid region of India - KANNAUJIA, PANKAJ KUMAR; DUKARE, AJINATH; KALE, SAKHARAM; NATH, PRERNA; SINGH, R K (The Indian Journal of Agricultural Sciences, 2023)
The influence of coloured-plastic mulching on physical and biochemical characteristics of tomato fruits were investigated. During the study, tomato crop was grown in an open field under five coloured-plastic mulching, one organic mulch and a no-mulch treatment. Harvested tomato fruits were analysed for various physico-chemical post-harvest quality parameters. Results evidenced that sphericity of tomatoe fruits was non-significantly (P